Molecular mechanism underlying the pathogenesis of NAFLD and NASH - Abdul Rahim, Roslina (2011)
Pioglitazone (PGZ) is a peroxisome proliferator-activated receptor (PPAR)-γ agonist that improves peripheral insulin sensitivity and reduces hepatocellular injury/ inflammation in non-alcoholic steatohepatitis (NASH). However, the underlying hepatic mechanism of action is not clearly understood with PGZ treatment. Therefore, liver biopsies were used to study genes, protein and immunohistochemistry expression of hepatocyte and hepatic stellate cell markers. PGZ decreased both αSMA and PPAR β expression in stellate cell and PPAR α hepatocyte expression, hence inhibit both stellate cell activation and β-oxidation in hepatocytes. PGZ also inhibit cell proliferation by reducing both PCNA and Ki67 in the liver. Up regulation of PPAR β, PXR, LXRα, IkBα and TNFRSF1B were observed (using Taqman Low density array gene expression), which indicates that PGZ exerts an anti-inflammatory and anti-fibrotic effect. PPAR β, PGC1α, ACADVL and UCP2 up regulation lead to increase β-oxidation and reduced reactive oxygen species (ROS) production. LXRα, ChREBP and SREBP1C activation leads to lipogenesis in the liver was also observed in PGZ treatment group. In vitro study was also conducted in freshly isolated human hepatic stellate cells, where these cells were incubated in vehicle and 5μM of PGZ for 72 hours consecutively. After 24 hours, 15ng/ml of PDGF-BB was incubated for 48 consecutive hours, followed by cell proliferation and gene expression analysis. PGZ up regulate the adipogenic genes expression followed by reduction in stellate cells marker expression and cell proliferation induced by PDGF-BB. PPAR β elevation after PGZ treatment in human liver and HSCs culture are novel findings in this study, but the role of PPAR β is clearly unknown in the liver and stellate cells. Therefore, similar treatment was performed using PDGF-BB on freshly isolated human HSCs, followed by treatment with PPAR β agonist (GW0742). GW0742 restores the adipogenic genes expression maintaining the quiescent phenotype of the stellate cell in contrast to previous study where PPAR β has been reported to cause stellate cells activation and proliferation. Overall, PGZ improved injury and fibrosis, inhibiting cell proliferation, increased both lipogenesis and β-oxidation in NASH patients. PGZ also inhibit stellate cells activation and proliferation and up regulated the adipogenic genes.